Climatology - Rohli, Robert V. (Jones & Bartlett Learning, 2015)
"Updated with the latest data from the field, Climatology, third edition presents students with a thorough introduction to the global climatic system. Written for upper-level undergraduate or introductory-level graduate courses, Climatology opens with an overview of climatology basics, including an introduction to the atmosphere and climate systems. The authors then delve into more advanced topics, like the global hydrologic cycle and general and secondary circulations, which are critical for understanding the processes that characterize climate across space and time. Closing with an in-depth look at climate change and the future of climatology, the text looks at sustainability from a climatologist's perspective and ties the climatic system to the rest of the earth-ocean-atmosphere system"--Provided by publisher -- Πηγή: Library of Congress